2018
DOI: 10.1038/s41467-018-05619-1
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the native major royal jelly protein 1 oligomer

Abstract: Honeybee caste development is nutritionally regulated by royal jelly (RJ). Major royal jelly protein 1 (MRJP1), the most abundant glycoprotein among soluble royal jelly proteins, plays pivotal roles in honeybee nutrition and larvae development, and exhibits broad pharmacological activities in humans. However, its structure has long remained unknown. Herein, we identify and report a 16-molecule architecture of native MRJP1 oligomer containing four MRJP1, four apisimin, and eight unanticipated 24-methylenecholes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 70 publications
(104 reference statements)
3
64
0
Order By: Relevance
“…As MRJP1 and apisimin form in RJ a complex with a stoichiometry of 4:4 (Mandacaru et al, ; Tian et al, ) and as relative transcript abundance is similar for both genes (Figure ), one would expect to quantify approximately the same molar amount of apisimin as MRJP1 at least in the HG at day 8. However, within the present study apisimin was not detected at all.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…As MRJP1 and apisimin form in RJ a complex with a stoichiometry of 4:4 (Mandacaru et al, ; Tian et al, ) and as relative transcript abundance is similar for both genes (Figure ), one would expect to quantify approximately the same molar amount of apisimin as MRJP1 at least in the HG at day 8. However, within the present study apisimin was not detected at all.…”
Section: Resultsmentioning
confidence: 98%
“…As MRJP1 and apisimin form in RJ a complex with a stoichiometry of 4:4 (Mandacaru et al, 2017;Tian et al, 2018) and as relative transcript abundance is similar for both genes (Figure S3) (Table S6). Within the brain, only MRJP1 was found within the 20 most abundant proteins at day 8 (37.8 ± 9.8 fmol; 5th place) (Table S6).…”
Section: Protein Amountsmentioning
confidence: 91%
See 2 more Smart Citations
“…The author found that MRJP-1 multimer was stable at 2°C or À18°C. According to the most recent findings, the core structure of the MRJP1 multimer consists of four molecules of MRJP1, four molecules of the peptide apisimin [34] and, surprisingly, eight molecules of 24-methylenecholesterol [35,36].…”
Section: Comparison Of Mrjp-1 Multimer and 10-hda Contents In Rj Sampmentioning
confidence: 99%